The Impact of Online Education on the Early Children's Learning Outcomes - Wahyuni, Wahyuni; Aulia, Prima (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2022)
This research is motivated by the existence of an online learning process in early childhood so that it impacts on children's learning outcomes. This study aims to determine the effect of online learning on early childhood learning outcomes at Raudhatul Athfal Islam Bakti 99 Nairatul Jannah Padang. This study uses quantitative and qualitative research techniques, namely the mixed method. The subjects in this study amounted to five people. Data collection techniques are in the form of interviews and questionnaires. This study uses quantitative data analysis techniques using level categorization, while qualitative data analysis uses coding approaches. And the outcomes of this study meant that there is an effect of online learning on early childhood learning outcomes. Quantitative and qualitative data supports these results. Quantitative data shows the impact of online education on learning outcomes in the moderate category. In contrast, while the results from qualitative data show that online learning partially affects children's learning outcomes so that learning outcomes tend to be less stable.